The Voice of the Farmer In Agricultural Extension: A Review of Beneficiary Assessments of Agricultural Extension and An Inquiry into their Potential as a Management Tool - Salmen, Lawrence F (AKIS Discussion Paper, 1999)

Foundations of the After Action Review Process - Morrison, John E; Meliza, Larry L (Special Report, 1999)
The U.S. Army has adopted the After Action Review AAR as its primary method of providing feedback after unit collective training exercises. The AAR is an interactive discussion in which unit members decide what happened, why it happened, and how to improve or sustain collective performance in future exercises. other services and organizations outside the military are also beginning to employ the AAR as a feedback tool. This report describes the twenty-five year history of AAR research and development and the major behavioral research areas contributing to AAR development and refinement. In addition, this report defines goals for future AAR research.

Using case studies to do program evaluation - Balbach, Edith D. (California Department of Health Services, 1999)
This paper, authored by Edith D. Balbach for California Department of Health Services is designed to allow evaluators to decide weather to use a case study evaluation approach. It also offers guidance on how to conduct a case study evaluation. Contents Using a Case Study as an Evaluation Tool 3 When to Use a Case Study 4 How to Do a Case Study 6 Unit Selection 6 Data Collection 7 Data Analysis and Interpretation 12

Introduction to Systems Thinking - Kim, Daniel H (Pegasus Communications, 1999)

Toward a Listening Bank: A review of best practices and the efficacy of Beneficiary Assessment - Salmen, Lawrence (Social Development Papers, 1998)
"This paper will first provide a descriptive overview of the beneficiary assessment (BA) work done on World Bank projects (by region, sector, phase of cycle, and so forth); it will then discuss impact, both qualitatively (with case studies) and quantitatively; and finally it will propose a course that, if taken, could lead to a Bank that truly listens and is attuned as much to the perspectives of the governments and peoples it serves as to the financial markets it helps sustain." "BAs use the qualitative techniques of conversational interviewing, focus groups, and participant observation with representative samples of key actors, such as the intended—usually poor—beneficiaries, service providers, non-governmental organizations (NGOs) and other local public- and private-sector leaders; analysis and the presentation of results are done as quantitatively as possible." Contents Beneficiary Assessment and the World Bank: An Overview Beneficiary Assessments in Africa Impact Case Studies Impact on Project Design Impact on Direct Cost Savings Summary of Quantifiable Impacts on Project Design and Objectives A Note on Methodology Complete the Paradigm Shift

PLA Notes 32: Participation, Literacy and Empowerment - PLA (Participatory Learning and Action Notes, 1998)

Who counts reality? Participatory monitoring and evaluation: A literature review - Estrella, M.; Gaventa, John (IDS Working Paper, 1998)

Participatory Monitoring & Evaluation: Learning from change - Guijt, Irene; Gaventa, John (IDS Policy Briefing, 1998)
Development organisations need to know how effective their efforts have been. But who should make these judgements, and on what basis? Usually it is outside experts who take charge. Participatory monitoring and evaluation (PM&E) is a different approach which involves local people, development agencies, and policy makers deciding together how progress should be measured, and results acted upon. It can reveal valuable lessons and improve accountability. However, it is a challenging process for all concerned since it encourages people to examine their assumptions about what constitutes progress, and to face up to the contradictions and conflicts that can emerge.

Complexity Rising: From Human Beings to Human Civilization, a Complexity Proﬁle - Bar-Yam, Yaneer (New England Complex Systems Institute, 1997)
It is generally recognized that life is becoming more complex. This article analyzes the human social environment using the "complexity proﬁle," a mathematical tool for characterizing the collective behavior of a system. The analysis is used to justify the qualitative observation that complexity of existence has increased and is increasing. The increase in complexity is directly related to sweeping changes in the structure and dynamics of human civilization—the increasing interdependence of the global economic and social system, and the instabilities of dictatorships, communism and corporate hierarchies. Our complex social environment is consistent with identifying global human civilization as an organism capable of complex behavior that protects its components (us) and which should be capable of responding eﬀectively to complex environmental demands.

A leaders's guide to after-action reviews - U.S. Army (Training Circular, 1993)
An after-action review (AAR) is a professional discussion of an event, focused on performance standards, that enables soldiers to discover for themselves what happened, why it happened, and how to sustain strengths and improve on weaknesses. It is a tool leaders and units can use to get maximum benefit from every mission or task. It provides- • Candid insights into specific soldier, leader, and unit strengths and weaknesses from various perspectives. • Feedback and insight critical to battle-focused training. • Details often lacking in evaluation reports alone. Evaluation is the basis for the commander's unit-training assessment. No commander, no matter how skilled, will see as much as the individual soldiers and leaders who actually conduct the training. Leaders can better correct deficiencies and sustain strengths by carefully evaluating and comparing soldier, leader, and unit performance against the standard. The AAR is the keystone of the evaluation process. Feedback compares the actual output of a process with the intended outcome. By focusing on the task's standards and by describing specific observations, leaders and soldiers identify strengths and weaknesses and together decide how to improve their performances. This shared learning improves task proficiency and promotes unit bonding and esprit. Squad and platoon leaders will use the information to develop input for unittraining plans. The AAR is a valid and valuable technique regardless of branch, echelon, or training task. Of course, AARs are not cure-alls for unit-training problems. Leaders must still make on-the-spot corrections and take responsibility for training their soldiers and units. However, AARs are a key part of the training process. The goal is to improve soldier, leader, and unit performance. The result is a more cohesive and proficient fighting force. Because soldiers and leaders participating in an AAR actively discover what happened and why, they learn and remember more than they would from a critique alone. A critique only gives one viewpoint and frequently provides little opportunity for discussion of events by participants. Soldier observations and comments may not be encouraged. The climate of the critique, focusing only on what is wrong, prevents candid discussion of training events and stifles learning and team building.

Case Study Evaluations - United States General Accounting Office (GAO, 1990)
his guide from the US General Accounting Office outlines good practice in case study evaluation and establishes a set of principles for applying case studies to evaluations. The paper outlines new ways of thinking about case studies and examines the methodology necessary to get the best from a case study analysis.